The Use of the Concept of Reciprocity for the Interpretation of Contemporary Advanced Industrial Societies: Ambiguities and Assets - Mingione, Enzo (ENDOXA, 2002)
The author rejects an mechanical application of reciprocity foranalysing social relations, both in past and current contexts. As the norm of reci procity is often invoked by the actors themselves, the research can reproduce actors’ interested representations of their relations. The paper indicates some of the problems involved.